2022
DOI: 10.1002/mgg3.1941
|View full text |Cite
|
Sign up to set email alerts
|

X‐linked hypophosphatemic rickets: Description of seven new variants in patients followed up in reference hospitals in Rio de Janeiro

Abstract: Background X‐linked hypophosphatemic rickets (XLHR) is a rare genetic disease, often delayed in diagnosis due to the low degree of suspicion and limited access to sophisticated diagnostic tools that confirm the diagnosis, such as genetic testing. Methods Through a cross‐sectional and observational study, 26 patients with a previously presumptive diagnosis of X‐linked hypophosphatemic rickets (based on clinical history, laboratory findings, and physical examination), were followed for approximately 12 months. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…A total of 23 different variants were distributed across the gene, and these variants have affected most exons or their adjacent introns (18). A major mutation density was found to be present from exon 15 to exon 22, corroborating with the findings of other studies (8,(26)(27)(28). Thus, the distribution in our cohort presents a lower mutation density in the first part of the gene according to PHEX mutation database (28).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A total of 23 different variants were distributed across the gene, and these variants have affected most exons or their adjacent introns (18). A major mutation density was found to be present from exon 15 to exon 22, corroborating with the findings of other studies (8,(26)(27)(28). Thus, the distribution in our cohort presents a lower mutation density in the first part of the gene according to PHEX mutation database (28).…”
Section: Discussionsupporting
confidence: 87%
“…In addition, the laboratory biomarkers were not strictly dependent on the type or site location of the variant. Popowska et al ( 27 ) found no relation between the severity of clinical symptoms and variant location. In concordance to that, no significant correlations were observed between the novel variant type and the serum concentrations of phosphate, PTH, or alkaline phosphatase at diagnosis, although one study reported that patients with truncating variants had lower serum phosphate concentration compared with patients without truncating variants ( 8 ).…”
Section: Discussionmentioning
confidence: 99%